Pemberian Edukasi kepada Masyarakat tentang Daun Cengkeh sebagai Tanaman Herbal dalam Penumbuh Rambut - Manuppak Irianto Tampubolon; Dhea Nur Fadhilah; Dumartina Hutauruk (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Clove leaves contain eugenol compound have properties to overcome hair growth problems. Public knowledge about herbal plants that had an effect on hair growth problems was still less. This community service was carried out to provide education to the public about clove leaves as herbal plants that can overcome hair problems. The method of community service was to provide education to the public through material exposure about clove leaves as herbal plants that overcome hair growth problems and introduce how to use clove leaves naturally. The results showed an increase in public knowledge in the use of herbal plants in Indonesia after providing education in the good category from 17.91% to 45.86%. Public knowledgestill lacking about herbal plants that could be used traditionally or processed into pharmaceutical preparations to prevent hair problems. The conclusion of community service in managing clove leaves as herbal plants to prevent hair problems meets the quantity and quality.